Flexible Hard Coating: Glass‐Like Wear Resistant, Yet Plastic‐Like Compliant, Transparent Protective Coating for Foldable Displays. Issue 19 (15th March 2017) - Choi, Gwang‐Mun; Jin, Jungho; Shin, Dahye; Kim, Yun Hyeok; Ko, Ji‐Hoon; Im, Hyeon‐Gyun; Jang, Junho; Jang, Dongchan; Bae, Byeong‐Soo
Abstract : A flexible hard coating for foldable displays is realized by the highly cross‐linked siloxane hybrid using structure–property relationships in organic–inorganic hybridization. Glass‐like wear resistance, plastic‐like flexibility, and highly elastic resilience are demonstrated together with outstanding optical transparency. It provides a framework for the application of siloxane hybrids in protective hard coatings with high scratch resistance and flexibility for foldable displays. Abstract : A flexible hard coating for foldable displays is realized by the highly crosslinked siloxane hybrid, using structure–property relationships in organic–inorganic hybridization. Glass‐like wear resistance, plastic‐like flexibility, and highly elastic resilience are demonstrated together with outstanding optical transparency. It provides a framework for the application of siloxane hybrids in protective hard coatings with high scratch resistance and flexibility for foldable displays.